2016
DOI: 10.4081/reumatismo.2015.849
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia gravis due to hydroxychloroquine

Abstract: <span lang="EN-US">No abstract available</span>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…Another question is whether hydroxychloroquine (HCQ) can be used in patients with pSS and MG. HCQ is an essential drug for patients with CTDs including SLE and SS, but special caution should be taken when used in MG patients. Although data from the Spanish society of Rheumatology Lupus Registry showed that HCQ protected against polyautoimmunity for patients with SLE ( 38 ), Varan et al reported a case of SLE in which MG developed with the use of HCQ, and regressed with its withdrawal ( 39 ). In a series of 17 patients with SLE and MG, Jallouli et al found that eight patients (47%) developed MG after initiation of HCQ, but only one patient who received HCQ had an exacerbation of myasthenic symptoms ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another question is whether hydroxychloroquine (HCQ) can be used in patients with pSS and MG. HCQ is an essential drug for patients with CTDs including SLE and SS, but special caution should be taken when used in MG patients. Although data from the Spanish society of Rheumatology Lupus Registry showed that HCQ protected against polyautoimmunity for patients with SLE ( 38 ), Varan et al reported a case of SLE in which MG developed with the use of HCQ, and regressed with its withdrawal ( 39 ). In a series of 17 patients with SLE and MG, Jallouli et al found that eight patients (47%) developed MG after initiation of HCQ, but only one patient who received HCQ had an exacerbation of myasthenic symptoms ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chloroquine and hydroxychloroquine have also been associated with new-onset or worsening MG and are typically used with caution in this patient group. 44,45 Azithromycin, a macrolide antibiotic, is also being used with chloroquine or hydroxychloroquine for COVID-19. Macrolide therapy, however, the most common being azithromycin, was not associated with reduced 90-day mortality or improvement in MERS-CoV RNA clearance in a study of patients with MERS.…”
Section: Ancillary Services/ Evaluationsmentioning
confidence: 99%
“…For this reason, we recommend a careful risk/benefit assessment before use in myopathic patients, and, in case of treatment with these agents, regular monitoring of serum CK levels. HCQ and azithromycin also have the potential to cause the onset or worsening of myasthenia gravis, and thus use in these patients should be carefully evaluated [65,90]. We do not recommend using these drugs as prophylaxis in NMD patients, as their prophylactic efficacy has not been proven and it may lead to serious toxicity [38].…”
Section: Treatments For Sars-cov-2 and Nmd Diseasesmentioning
confidence: 99%